Prevalence of Congenital Heart Disease in Xinjiang Multi-Ethnic Region of China - Liu, Fen; Yang, Yi-Ning; Xie, Xiang; Li, Xiao-Mei; Ma, Xiang; Fu, Zhen-Yan; Chen, Bang-Dang; Huang, Ying; Shan, Chun-Fang; Ma, Yi-Tong; Gao, Xiao-Ming (PLOS ONE, 2015)
Background The prevalence and risk factors of congenital heart disease among Xinjiang, northwestern part of China is currently unknown. Methods This multiple-ethnic, community-based, cross-sectional study was conducted to estimate the prevalence and distribution of congenital heart disease (CHD) in Xinjiang, northwestern part of China. Four major ethnics, Uygur, Han, Kazak, and Hui children in this region were investigated during February 2010 and May 2012. Results A total of 14,530 children (0–18 yr) were examined. Of these children, 240 (boys, 43.8%, and girls, 56.3%) were identified with CHD, giving an overall prevalence of 16.5‰ (17.7‰ in Uygur, 6.9‰ in Han, 11.4‰ in Kazak, and 38.1‰ in Hui Chinese, respectively). Ventricular septal defect (VSD, 29.2%), atrial septal defect (ASD, 20.8%), patent ductus arteriosus (PDA, 13.7%), acleistocardia (13.7%), Bicuspid aortic valve (7.9%), pulmonary valve stenosis (5.4%), and tetralogy of fallot (TOF, 4.2%) were common cyanotic and cyanotic defects observed. Compared to non-CHD children, children with CHD had a higher percentage of history of abortion, CHD history of family, consanguinity and premature birth (all P<0.05). In CHD children, 24% of mothers caught a cold, 10% had a febrile illness and 6.7% received antibiotic treatment during the first trimester of pregnancy, that were higher than non-CHD group (all P<0.05). Conclusion The overall prevalence of CHD in four ethnic children at ages 0–18 yr in Xinjiang was 16.5‰. VSD, ASD and TOF were the most common acyanotic and cyanotic congenital heart defects, respectively. This study also identified some modifiable risk factors that may contribute to the incidence of CHD among the 4 ethnic groups.